Research of the device design for sorting of railway vehicle at station which serves large metallurgical industrial complex - Берестов, Ігор В’ячеславович; Розсоха, Олександр Володимирович; Куценко, Максим Юрійович; Бордюг, Олена Анатоліївна; Потюк, Юрій Олексійович (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of hump necks construction of native marshalling yard’s of railway station Mariupol-Sortuvalnyj mechanism made: they do not completely meet the demands, written in Rules and standards in force in design of marshalling yard’s mechanisms. That’s why in many cases it is impossible to use saving resources ways without full reconstruction of the head marshalling yard